If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -1x + 2 = -3 Reorder the terms: 6 + 2 + -1x = -3 Combine like terms: 6 + 2 = 8 8 + -1x = -3 Solving 8 + -1x = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1x = -3 + -8 Combine like terms: 8 + -8 = 0 0 + -1x = -3 + -8 -1x = -3 + -8 Combine like terms: -3 + -8 = -11 -1x = -11 Divide each side by '-1'. x = 11 Simplifying x = 11
| Y=21x+98 | | 6-6a=-6-5a+5 | | 7/3x+2/5= | | 2x=77 | | y+.8=.6(y+4) | | 3+2x+5=-17 | | 3(2t+2)= | | y=0.2x^3-5 | | -2xb= | | 2m+9=90 | | f(x)=-4cos(x) | | 6y-16=90 | | f(-x)=7x^2+3x-8 | | 518=vot-16t^2 | | 5x+7=x-17 | | 518=vot-16t | | 6x-(2)=26 | | 5(x-2)=8x-x | | p=4x+450 | | 0.3X-1.8=-5.04 | | -10=3f+2f | | 14+7x-6-15x+5=5x+7-12x+5-12 | | S=c+xv | | 2y-4y=6 | | 29+4y-3=17y-14-5y | | (3x-6)=(x+10) | | 5k+12+k=x+28 | | 13f+6=-5 | | 2*(2a+3)=18 | | -9*2-3(-56+12*2)=78 | | u=7(3n+31)+9(n+1) | | =x^2+17x+72 |